2014
DOI: 10.1371/journal.pone.0098717
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetic Compatibility of Ginsenosides and Schisandra Lignans in Shengmai-san: From the Perspective of P-Glycoprotein

Abstract: BackgroundPhytochemical-mediated alterations in P-glycoprotein (P-gp) activity may result in herb-drug interactions by altering drug pharmacokinetics. Shengmai-san, a traditional Chinese herbal medicine composed by Panax Ginseng, Ophiopogon Japonicus, and Schisandra Chinensis, is routinely being used for treating various coronary heart diseases. In our previous studies, Schisandra Lignans Extract (SLE) was proved as a strong P-gp inhibitor, and herein, the compatibility of Shengmai-san was studied by investiga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 33 publications
0
20
0
Order By: Relevance
“…The minister drug helps strengthen the curative effect of the monarch drug, or, is used for treatment of accompanying symptoms [41]. The assistant drug is used to promote the treatment efficacy of the minister drug on chief syndromes/disease, or to aim at minor symptoms [42]. The Guide drug is to lead the ‘herbs’ impact to the disease location and to modulate the interaction among the herbs [43].…”
Section: Resultsmentioning
confidence: 99%
“…The minister drug helps strengthen the curative effect of the monarch drug, or, is used for treatment of accompanying symptoms [41]. The assistant drug is used to promote the treatment efficacy of the minister drug on chief syndromes/disease, or to aim at minor symptoms [42]. The Guide drug is to lead the ‘herbs’ impact to the disease location and to modulate the interaction among the herbs [43].…”
Section: Resultsmentioning
confidence: 99%
“… 26 Located in the apical membrane of several barrier epithelia, including the intestine, renal epithelial cells, bile canalicula, and the brain capillary endothelial cells, P-gp’s inhibition or induction may be responsible for drug interactions with phytomedicines. 27 Changes in the levels of P-gp were measured in renal tissue by Western blotting assay. The results showed that P-gp level was intensively increased when rats were exposed to CsA when compared with vehicle control rats ( Figure 10 , P <0.001).…”
Section: Resultsmentioning
confidence: 99%
“…al. have showed that the e ux ratios of some ginsenosides, e.g., Rh1, F1, Re, and Rg1, were not affected by verapamil (48). This may be due to the different structures of ginsenosides and existence of other transporters involved in the absorption of certain ginsenosides.…”
Section: Discussionmentioning
confidence: 99%